Soil organic matter in sustainable agriculture (CRC Press, 2004)
This textbook contains evaluations of the types of organic soil constituents-organisms, fresh residues, and well-decomposed substances. It explores the beneficial effects of organic matter on soil and the various practices that enhance SOM. Chapters include an examination of the results of crop management practices on soil organisms, organic matter gains and losses, the significance of various SOM fractions, and the contributions of fungi and earthworms to soil quality and crop growth